Public and Private Utilisation of In-Patient Beds in Irish Acute Public Hospitals - O'REILLY, JACQUELINE; WILEY, MIRIAM (ESRI, 2011)
Health care systems in many developed countries have services financed and provided by both public and private sectors. In Ireland, though, the public/private mix is atypical: a private patient can be treated in an acute public hospital and seen by a consultant who may also treat public patients within the same hospital. Nationally, one in five beds in acute public hospitals is designated for use by private patients and existing legislation restricts accommodation of a private patient in a public-designated bed. Yet there are concerns that acute public hospitals may sidestep such restrictions on their private practice, resulting in public hospital resources potentially being diverted away from public patients towards their private counterparts. Indeed, Irish providers face financial incentives which favour the treatment of private patients. Consultants are rewarded on a fee-for-service basis for private care, but receive a salary for public practice. Public hospitals, meanwhile, receive a fixed daily payment for every private patient in a private bed. Added to these financial incentives is an increased opportunity to engage in private practice due to the substantial recent growth in private health insurance subscribers.
PUBLISHED
Dublin
ESRI Research Bulletin 2010/04/05
Keywords: Social Policy; Health Care